High intradialysis diastolic blood pressure variability is an independent predictor of all-cause mortality - Wei Wang; Yuehong Li; Xianglan Wu; Wen Wen; Huiying Xu; Jiaxuan Lv (Annals of Medicine)
Background To investigate the relationship between intradialytic blood pressure variability (BPV) and all-cause mortality in patients on maintenance hemodialysis (MHD).Methods Intradialysis blood pressures and other clinical characteristics of 142 MHD patients who were on dialysis from 08/2016 to 07/2017 were retrospectively collected. Death events were followed and recorded in the following at least 36 months. The systolic/diastolic blood pressure coefficient of variation (SBPCV/DBPCV) and the systolic/diastolic average real variation of blood pressure (SBPARV/DBPARV) were calculated. Univariate and multivariate Cox proportional hazards models were used to examine the relationship between intradialytic BPV and all-cause mortality.Results Among the 142 MHD patients (age 61.5 ± 15.0 years, males 63.6%). High BPV, including the SBPCV and DBPCV at the beginning of dialysis, intradialytic SBPCV and DBPCV, intradialytic DBPARV, and the DBPCV at the end of dialysis, were significantly associated with all-cause death (p < 0.05) while no association was noted between high intradialytic SBPARV and SBPCV and all-cause death. However, after adjusted for age, history of cardiovascular disease, serum sodium, prealbumin, albumin, hemoglobin level and standardized ultrafiltration volume, high intradialytic DBPARV was associated with worse time-dependent death (HR 2.762 [95% CI: 1.273–5.993], p = 0.010). And DBPARV was positively correlated with ultrafiltration volume (r = 0.219, p = 0.009).Conclusions High intradialytic DBPARV was an independent risk factor for all-cause mortality. Intradialysis BPV is mainly impacted by ultrafiltration volume.